2019
DOI: 10.3389/fnagi.2019.00314
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and Rapamycin Attenuate Isoflurane-Induced Cognitive Impairment Through Inhibition of Neuroinflammation by Suppressing the mTOR Signaling in the Hippocampus of Aged Mice

Abstract: Melatonin exerts neuroprotective effects on isoflurane-induced cognitive impairment. However, the underlying mechanism has yet to be elucidated. The present study sought to determine if melatonin confers its beneficial effects by acting on mammalian target of rapamycin (mTOR) and attenuates the neuroinflammation in the hippocampus of aged mice. A total of 72 male C57BL/6 mice, 16-month-old, were randomly and equally divided into six groups: (1) the control group (CON); (2) the rapamycin group (RAP); (3) the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 47 publications
2
16
0
Order By: Relevance
“…Lipopolysaccharide as cytokine inducer evoke peripheral and central immune activation in animal leading to neuroinflammation, accompanied by depressive-like behaviors (Sekio and Seki, 2015;Micheli et al, 2018;Zhao X. et al, 2019). In agreement with the previous findings (Raghavendra et al, 2000;Yu et al, 2017;Yuan et al, 2019), our results demonstrated depressive-like behaviors upon LPS-treatment, which was reversed by melatonin treatment. Besides, LPS dysregulates PI3K/Akt/GSk3b signalings, which plays a crucial role in survival, proliferation, and invasion by generating the second messengers (Guijarro-Munoz et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Lipopolysaccharide as cytokine inducer evoke peripheral and central immune activation in animal leading to neuroinflammation, accompanied by depressive-like behaviors (Sekio and Seki, 2015;Micheli et al, 2018;Zhao X. et al, 2019). In agreement with the previous findings (Raghavendra et al, 2000;Yu et al, 2017;Yuan et al, 2019), our results demonstrated depressive-like behaviors upon LPS-treatment, which was reversed by melatonin treatment. Besides, LPS dysregulates PI3K/Akt/GSk3b signalings, which plays a crucial role in survival, proliferation, and invasion by generating the second messengers (Guijarro-Munoz et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have suggested that the process of autophagy is negatively regulated by the activation of mTOR (Kim et al, 2011;Alers et al, 2012;Abada and Elazar, 2014). Numerous studies have shown that the role of mTOR signaling in protein homeostasis appears to be particularly important in learning and memory function (Bavley et al, 2018;Gao et al, 2018;Yuan et al, 2019). In the present study, we found that the levels of p-mTOR increased and Beclin-1 and LC3-II decreased in the hippocampus of mice undergone anesthesia/surgery.…”
Section: Discussionsupporting
confidence: 65%
“…An experimental study showed that melatonin administration effectively prevented mild inflammation in high-fat diet-induced metabolic syndrome (MS) rats [ 35 ]. Through inhibition of neuroinflammation, melatonin can attenuate cognitive impairment induced by various pathological conditions [ 36 , 37 ]. Besides, the anti-inflammatory action of melatonin might be associated with its antiobesity effect.…”
Section: Discussionmentioning
confidence: 99%